2016
DOI: 10.1007/s00125-016-4189-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and intensive physical activity reduces risk of cardiovascular events in type 1 diabetes

Abstract: Aims/hypothesis Cardiovascular disease (CVD) is the most common cause of premature death and disability among patients with type 1 diabetes. Diabetic nephropathy accounts for the increased cardiovascular morbidity and mortality of these patients. We recently showed that the intensity of exercise predicts the incidence and progression of diabetic nephropathy in patients with type 1 diabetes. Little is known about the relationship between physical activity and CVD. Therefore, we studied how physical activity aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 23 publications
0
37
0
6
Order By: Relevance
“…Randomized trials have found that supervised exercise interventions improve glycated hemoglobin (A1C) (6)(7)(8), triglycerides (TG) and cholesterol (9) in people with type 2 diabetes when compared to no exercise comparison groups (10). Cohort studies have demonstrated that, in people with type 2 (11)(12)(13), and with type 1 diabetes (14,15), regular physical activity (11)(12)(13) and/or moderate to high cardiorespiratory fitness (16) are associated with reductions in cardiovascular (CV) and overall mortality.…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%
“…Randomized trials have found that supervised exercise interventions improve glycated hemoglobin (A1C) (6)(7)(8), triglycerides (TG) and cholesterol (9) in people with type 2 diabetes when compared to no exercise comparison groups (10). Cohort studies have demonstrated that, in people with type 2 (11)(12)(13), and with type 1 diabetes (14,15), regular physical activity (11)(12)(13) and/or moderate to high cardiorespiratory fitness (16) are associated with reductions in cardiovascular (CV) and overall mortality.…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%
“…Nevertheless, there is less information regarding type 1 diabetic patients. A recent report indicates that intense exercise is associated to reduction in the risk of cardiovascular events in type 1 diabetes patients [16]. In animal models of type 1 diabetes, low-to-moderate exercise training has been found to improve cardiac glucose metabolism [17], reduce apoptosis [18], and improve ventricular function [19].…”
Section: Introductionmentioning
confidence: 99%
“…Next, regular physical activity reduces insulin resistance and insulin requirement, it also results in improvement in lipid profile and endothelial function . Finally, physically active people with T1DM are less likely to develop macrovascular complications and have lower mortality rates . A recently published cross‐sectional multicentre study on 18 028 T1DM individuals showed that physical activity improved long‐term glycaemic control .…”
Section: Discussionmentioning
confidence: 99%